Developing High Order Competencies in Students Through the Integration of Research-Oriented Activities (Journal of Asian Development Studies, 2025)
Developing higher-order skills (HOS), such as critical thinking, creativity, and problem-solving, is essential for students to thrive in today's dynamic and competitive environment. This study examines the effectiveness of project-based learning (PBL), inquiry-based learning (IBL), and mentoring in developing HOS among students and identifying the best ROA for achieving such development. A quantitative research design was used, and self-developed questionnaires were employed for the data collection. Purposive random sampling was used to get data from 317 high school respondents. The instrument's reliability was measured using a Cronbach's alpha of 0.93, indicating a high internal consistency. The findings revealed that PBL and IBL are highly effective in promoting critical and creative thinking, while mentoring has limited direct support for HOS. The structural equation modelling (SEM) results showed that research activities are the best predictors of HOS (β = .79, p < .01), explaining 62% of the variance. At the same time, mentoring has a weak but significant relationship with research activities and no direct impact on HOS. Promoting PBL, IBL, and mentoring in educational practices is highly emphasized. The integration of mentoring with structured ROA is recommended for its improvement in effectiveness, followed by investment in teacher training programs and addressing geographic disparities in educational resource allocation. In adopting these measures, they prepare the complete learning atmosphere with skills that students require to deal with real-world challenges and to excel in interdisciplinary environments.